ANALISIS HARGA PASOK, KUALITAS LAYANAN DAN KEMUDAHAN TERHADAP LOYALITAS PETANI TEBU GONDANGLEGI KABUPATEN MALANG - Ardianto, Yusaq Tomo (IQTISHODUNA, 2010)
This research was conducted in August 2009. Commodities have certain sugarcane proved good prospects for sugar prices from year to year continue to increase. This is expected to have a balance between sugarcane farmers' income with the increase in sugar prices. In general, the purpose of this study was to test how much influence the supply price policy, quality of services and facilities conducted by the New Krebet PG for sugarcane farmers around South Malang Regency. Results showed that the policy affects the supply price of sugarcane farmers and the loyalty of service quality did not provide a positive impact on the loyalty of sugarcane farmers. This research hopes to PG policy New Krebet always siding with the interests and the fate of sugarcane farmers and factory environments around the intertwined relationships of a harmonious partnership between sugar cane farmers by the factory.